Representing Aboriginal Self-Government and First Nations/State Relations: Political Agency and the Management of the Boreal Forest in Eeyou Istchee - Salée, Daniel; Lévesque, Carole (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractThis paper is primarily concerned with the way in which the strategies Indigenous peoples choose to address and deal with state power are being characterized by recent scholarly assessments of territorial and self-government agreements in Canada. The authors contend that by emphasizing almost exclusively seemingly irreversible structural determinants (such as colonialism and the capitalist logic of dispossession), the interpretative orientation of that literature tends to misrepresent the nature and dynamics of First Nations politics in the Canadian context and minimizes the positive impact of their action on social change. On the basis of an examination of contentious politics and the resulting institutional practices elaborated in relation to the management of forest resources and environmental policy in Eeyou Istchee (land of the James Bay Cree) over the past 30 years, the paper underscores instead the Cree’s political agency and their ability to secure a substantial measure of control over the management of forest resources and the definition of environmental policy. It argues that the Cree have largely succeeded in reversing the historical logic of domination to which Indigenous peoples have been submitted and in reappropriating key instruments of collective empowerment. The paper ultimately offers a defence for an analytical stance that appreciates First Nations’ political and policy choices from the perspectives of what they actually mean for the communities involved rather than from the point of view of normative and theoretical absolutes.